Compositional changes of casein micelles induced by calcium or chelatant addition at threefold and natural casein concentration. (July 2022) - Reiter, Marius; Reitmaier, Michael; Kulozik, Ulrich
Abstract: Milk protein concentrates are gaining importance in dairy products design and manufacture. The effect of adding CaCl2 or trisodium citrate (TSC) at various concentrations to micellar casein concentrate (MCC) with threefold concentrated casein micelles (CM) was assessed and compared with natural casein concentration. CM in MCC and in a skim milk-like system (MLC) were analysed regarding soluble and sedimentable casein, micellar calcium, phosphate, and micelle hydration. We hypothesised that casein micelles in MCC are less affected by these milieu changes. In fact, concentrated CM showed less pronounced compositional changes induced by TSC and CaCl2 addition. CM in MCC were less saturated in calcium and phosphate at higher levels of CaCl2 addition than in MLC. 94.2% of the CM remained intact up to 15 mm TSC addition, but only 41.5% CM in MLC. This study yields a wider understanding of CM if applied in concentrated form and provides options for modifying their functionalities.